Investigating the molecular mechanisms, drug prediction, and validation of CCNA2 and MAD2L1 in esophageal squamous cell carcinoma based on bioinformatics - Chenfan Guo; Pandeng Wang; Diemei Huang; Jianji Guo; Tao Liu (BMC Medical Genomics)
Abstract Objective Aims to comprehensively investigate the expression patterns of CCNA2 and MAD2L1 in esophageal squamous cell carcinoma using bioinformatics methods. Methods Based on WGCNA analysis of gene mutation expression, methylation level distribution, mRNA expression and ESCC-related genes in public databases, were employed for investigating potential biomarkers for prognosis of esophageal squamous cell carcinoma(ESCC).Finally,. performing qRT-PCR and immunohistochemistry to validate. Results Ultimately identified 4 hub genes: CDK1, CCNA2,TOP2A and MAD2L1. Bioinformatics analysis showed high expression of these four genes in ESCC (P < 0.05). CCNA2 and MAD2L1 were selected for subsequent analysis based on literature.3.Single gene enrichment analysis revealed significant enrichment of CCNA2 and MAD2L1 in pathways related to splicing, bladder cancer, non-homologous end joining and homologous recombination, glycosaminoglycan biosynthesis chondroitin sulfate, progesterone-mediated oocyte maturation and mismatch repair. PASTAA database indicated the involvement of transcription factors such as Roralpha1, Pou6f1, Roralpha2, Atf-1, Pax-3, C/ebpalpha, Nkx2-1 in the regulation of CCNA2, while no transcription factors were predicted for MAD2L1..Immune infiltration analysis revealed a close association between ESCC and plasma cells, CD8 + T cells, monocytes, M0 macrophages, M1 macrophages, dendritic cells, and resting mast cells.Drug prediction for CCNA2 included 7 drugs such as ETHINYL ESTRADIOL, Seliciclib and TAMOXIFEN, while no drugs were predicted for MAD2L1.qRT-PCR and immunohistochemistry demonstrated high expression of CCNA2 in ESCC, while MAD2L1 showed no significant difference between ESCC and normal esophageal squamous epithelial tissues. Conclusion CCNA2 and MAD2L1 may be potential biomarkers for ESCC, providing a novel basis for understanding the molecular mechanisms underlying ESCC pathogenesis.Additionally, the potential drugs predicted for CCNA2 may emerge as a new hope for ESCC patients in the future.